First (e, e) coincidence measurements on solvated sodium benzoate in water using a magnetic bottle time-of-flight spectrometer. Issue 16 (9th December 2022) - Huart, L.; Fournier, M.; Dupuy, R.; Vacheresse, R.; Mailhiot, M.; Cubaynes, D.; Céolin, D.; Hervé du Penhoat, M. A.; Renault, J. P.; Guigner, J.-M.; Kumar, A.; Lutet-Toti, B.; et al.
Abstract : Sodium benzoate molecules solvated in water are studied using coincidence electron spectroscopy coupled with a liquid microjet device. Abstract : Understanding the mechanisms of X-ray radiation damage in biological systems is of prime interest in medicine (radioprotection, X-ray therapy…). Study of low-energy rays, such as soft-X rays and light ions, points to attribute their lethal effect to clusters of energy deposition by low-energy electrons. The first step, at the atomic or molecular level, is often the ionization of inner-shell electrons followed by Auger decay in an aqueous environment. We have developed an experimental set-up to perform electron coincidence spectroscopy on molecules in a water micro-jet. We present here the first results obtained on sodium benzoate solutions, irradiated at the oxygen and carbon K-edges.